Predict potential pharmacological mechanisms of Ling-gui-Zhu-gan Decoction in treating unstable angina pectoris using liquid chromatography-mass spectrometry and network pharmacology - Li, Xiaopeng; Xue, Tan; Zhang, Panpan; Dong, Fengyu; Li, Han; Yao, Jing; Huang, Haiying; Zhang, Lizhuang; Liu, Ruixin (Frontiers in Chemistry, 2025)
IntroductionLing-Gui-Zhu-Gan Decoction (LGZGD), one of the first batches of classical Chinese prescriptions formally recognized by the Chinese government, has a long-standing history of clinical application and significant potential for modern development. However, the chemical composition and content of different types of pharmaceutical preparations are not clear.MethodsThis study aimed to develop an analytical approach integrating HPLC and UHPLC-Q-Orbitrap/MS to comprehensively characterize the chemical constituents of LGZGD across different preparation stages and to investigate its pharmacodynamic basis in the treatment of unstable angina pectoris (UA) using network pharmacology. The content and transfer rate of six index components were quantified using HPLC.ResultsA total of 75 compounds were identified via UHPLC-Q-Orbitrap/MS, comprising 24 flavonoids, 25 organic acids, nine phenylpropanoids, eight terpenoids, five saponins, and four other compounds, based on precursor ion peaks and fragment ion spectra. Notably, five compounds—(-)-pterocarpin glucoside, γ-aminobutyric acid, calycosin, trimethyl citrate, and proline-phenylalanine—were absent following the drying of the concentrate. Using the LC-MS data as a foundation, network pharmacology and molecular docking analyses were conducted to elucidate the pharmacodynamic components responsible for LGZGD’s therapeutic effects on UA. This integrative analysis identified three key active compounds—naringenin, glycyrrhizin, and calycosin—and three core targets: TNF, EGFR, and PTGS2.DiscussionThe analytical method established in this study effectively delineates the chemical profile and index component transfer dynamics of LGZGD preparation intermediates, providing essential data for the development of both liquid and solid dosage forms. The constructed “medicine-component-target-pathway-disease” network preliminarily reveals the multi-component, multi-target, and multi-pathway mechanisms by which LGZGD may exert therapeutic effects on UA. This work provides a scientific foundation for its clinical application, supporting rational drug use and formulation development.